2011
DOI: 10.1088/0031-8949/83/05/055703
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic electro-optic effects and electro-absorption process in multilayer nanoshells

Abstract: In this corrigendum, the authors would like to report typographic errors in the first name of the second author and in equation 7.The first name of the second author should have been written Fereshteh instead of Fatemeh.In equation 7 the parameter k nl,2 should have been written

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…When the thickness of the inner or outer shell increase, energy distances between electronic states become smaller. Therefore, the size of the inner or the outer shell grows, the energy distance shrinks, and the dipole matrix element m [31,45] and susceptibility is plotted as a function of pump photon energy ÿω (eV) for various d 2 while R 1 =d 1 =d 3 =1 nm in the case E<V c . Both the magnitude of the peak and its position depend on the middle shell thickness.…”
Section: Resultsmentioning
confidence: 99%
“…When the thickness of the inner or outer shell increase, energy distances between electronic states become smaller. Therefore, the size of the inner or the outer shell grows, the energy distance shrinks, and the dipole matrix element m [31,45] and susceptibility is plotted as a function of pump photon energy ÿω (eV) for various d 2 while R 1 =d 1 =d 3 =1 nm in the case E<V c . Both the magnitude of the peak and its position depend on the middle shell thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, much consideration has been given to the third order optical nonlinearity in the QD nanostructures. Various studies have investigated the third order nonlinear optical susceptibility (TONOS) using experimental methods [18,19] or theoretical approaches [20][21][22][23][24][25][26]. The results revealed that, the TONOS is largely controlled by the size and shape of the nanodot, the incident photon energy, the relaxation time and the molar concentration of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…As for theoretical works, the magnetic and electric field effects on the binding energy of a shallow donor confined to move in spherical QDQW is studied in Rahmani et al (2009), and quadratic electro-optic effects and electroabsorption process in multilayer nanoshells is discussed in Bahari and Moghadam (2011). In the previous works of the author with co-authors the influence of weak external uniform (Harutyunyan 2003(Harutyunyan , 2007Harutyunyan et al 2004a) and radial (Harutyunyan 2002;Harutyunyan et al 2004b) electrostatic fields on the electronic and optical properties of QDQWs are examined theoretically.…”
Section: Introductionmentioning
confidence: 99%